Penanda Kohesi Gramatikal dalam Novel Anak Rantau Karya Ahmad Fuadi - Intan Yuniar; Novia Juita (Faculty of Languages and Arts, Universitas Negeri Padang, 2020)
This study aimed to described the markers of grammatical cohesion in Ahmad Fuadi's novel Anak Rantau and to explain the dominant markers of grammatical cohesion found in Ahmad Fuadi's novel Anak Rantau. This type of research because the data is in the form of languange units (paragraphs, sentences, clauses, and phrases) which contain grammatical cohesion markers. The data source of this research is from the novel Anak Rantau by Ahmad Fuadi. Methods and technique the research data collection use the observation and note method and technique used, namely the tapping technique. The findings of this study are, first, the four markers of grammatical cohesion in Ahmad Fuadi's novel Anak Rantau by: (a) references or referred to as references are divided into three type, including: personal pronouns, demonstrative references, and comparative references. (b) conjuction and liaison is divided into three types, namely: liaison between clauses, liaison between sentences, and liaison between paragraphs. (c) substitution or what is commonly called restitution is divided into four types, nominal substitution, verbal substitution, fractal substitution, and clausal substitution. (d) ellipsis or impingement. Second, the dominant grammatical cohesion marker found in Ahmad Fuadi's novel Anak Rantau, namely the references contained in personal pronouns or what can be called a persona reference was found as many as 1193 data. The author of the novel mostly uses personal pronouns, especially in the pronoun persona III (third) closely bound form, namely 797 data found and mostly refers to the character Hepi and Lenon.